MEDIA VISUAL - KINESTETIK UNTUK MENINGKATKAN HASIL BELAJAR BAHASA ARAB SISWA - Rodhi, Ahmad (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2016)
This research is a Classroom Action Research. The purpose of Classroom Action Research that I conducted is to know that learning with visual-kinesthetic media can improve students' Arabic learning outcomes, viewed from the cognitive, affective and psychomotor aspects. The subjects in this study are students, teachers, head of madrasah and administrative staff. As for the data collection, I used observation, interviews, and tests. This study was conducted in 3 cycles with 5 meetings. Each cycle consists of four stages: planning, implementation, observation, and reflection. The results of this study indicate that the use of visual-kinesthetic media can improve students' Arabic learning outcomes in cognitive, affective and psychomotor domains.